Unit-circle-preserving mappings - Soon-Mo Jung; Byungbae Kim (International Journal of Mathematics and Mathematical Sciences)
We prove that if a one-to-one mapping f:ℝn→ℝn(n≥2) preserves the unit circles, then f is a linear isometry up to translation.